PEMANFAATAN DAN UPAYA KONSERVASI KAYU PUTIH (Asteromyrtus symphyocarpa) DI TAMAN NASIONAL WASUR - Yarman .; Ellyn K. Damayanti (Media Konservasi, 2012)
Asteromyrtus symphyocarpa synonym with Melaleluca symphyocarpa of the Myrtaceae family is an endemic plant at Northern Australia, South Papua (Indonesia,) and Papua New Guinea. Wasur National Park (South Papua District, Papua, Indonesia) is one of  A.symphyocarpa’s  distribution areasTwo villages in Wasur National Park, namely Yanggandur Village and Rawa BiruVillage have been  performing utilization of A. symphyocarpa with the process of distillation.  Today, the utilization of A. Symphyocarpa has become one of livelihoods sources for the peoples in this region.  However, A. symphyocarpain Wasur National Park was facing a high level of threats, the mostly are: habitat destruction, habitat fragmentation, habitat degradation, and the invasion of alien species.  This paper was aimedat  exploringother potential uses of A. symphyocarpa in addition to its essential oil and also to formulate conservation efforts in Wasur National Park. The analysis is was done through literature  studies and  authors’  experiences.  An alternative solution to preserve this species is was to developmentof  stakeholders’ participation.  Those stakeholders must be involved actively of performingin  the real conservation efforts. Key words: Asteromyrtus symphyocarpa, utilization, threats, conservation, Wasur National Park